A possible mechanism for manganese release from acid soil - Miyazawa, Mário; Pavan, Marcos A.; Neto, Ladislau Martin (Pesquisa Agropecuaria Brasileira, 1993)
The objective was to study the principal mechanism responsible for Mn solubility in acid soils in the State of Paraná, Brazil. Air-drying, heating, autoclaving and oxidation with H2O2 in soil samples increased Mn solubility. Soluble Mn after drying or sterilizing soil sample was reimmobilized, respectively, by wetting with water or adding soil solution obtained from natural soil. Sterilized soil kept dried or wet with sterilized water did not show Mn re-immobilization. The strength of extraction solution was the following: EDTA > CuCl2 > Oxalic acid > MgCl2. The Mn solubility was controlled by Mn-organic ligant stability complex. Under natural conditions the content of soil organic ligant is maintained by biological activity. Mn-organic complexing reaction was probably the main mechanism responsible for the control of Mn solubility in acid soils in the State of Paraná.